Arbuscular mycorrhizal and native dark septate fungus in jerusalem artichoke (Helianthus tuberosus L.) in Catamarca, Argentina - Di Barbaro, Gabriela; Andrada, Horacio; González Basso, Valeria; Alurralde, Ana Lilia; Del Valle, Eleodoro; Brandán de Weht, Celia (Revista de Ciencias Agrícolas, 2017)
In order to determine and evaluate the fungal root infection it was studied the colonization by native fungal symbionts in roots of jerusalem artichoke (Helianthus tuberosus L.) cultivated in the Central Valley of the province of Catamarca, an arid region at the Northwest of Argentina. The studies were made by: microscope observation of the stained root fungal structures. The infection quantification was made by clarification methodologies and count under magnifying glass. Endomycorrhizal structures of the vesicle arbuscular type were observed (MVA; hyphae, arbuscules and vesicles) and of septate dark endophytic fungi (DES; melanized septate hyphae and with numerous microesclerotia). A high level of fungi colonization was determined with simultaneous occurrence of vesicle arbuscular mycorrhizae (VAM) and fungi (DES). This study is the first report of the colonization by VAM and DES in roots of jerusalem artichoke.